Evolución de los parámetros geométricos de diseño en puentes construidos con voladizos sucesivos in situ (2016)
Cast-in-place bridges built using the cantilever method have been studied and evaluated. Also the theories used for their pre-dimensioning from 1978 to the present were compared, like the evolution of its design. The data were collected and obtained of transverse and longitudinal sections of 124 cast-in-place bridges built using the cantilever method in 29 countries and were subsequently evaluated. These 124 bridges are condensed into three groups by chronology, free span and by countries. These data are processed statistically and compared with classical values used in design. The analysis of results allows for parametric graphs associated with the design conditions. The conclusions shows how varying the geometric design parameters in time and how they will obtain optimal values that allows to design and build safer and economic bridges